Current Status and Future Trends in Installation, Operation and Maintenance of Offshore Floating Wind Turbines - Mingfeng Hu; Jinkun Shi; Sheng Yang; Mingsheng Chen; Yichang Tang; Suqian Liu (Journal of Marine Science and Engineering, 2024)
The installation and operation phases are critical stages in the lifecycle of offshore wind turbines, with costs associated with the installation and maintenance of floating wind turbines accounting for approximately 50% of the total investment. This paper presents the latest advancements in the technologies for the installation and maintenance of floating wind turbines. First, it discusses the installation techniques and relevant research related to the foundations and components of floating wind turbines. Next, it explores various operational strategies for offshore wind turbines and studies on major component replacements. The interrelationship of research in the installation and maintenance fields for floating wind turbines is examined. Furthermore, this paper investigates various tools and equipment used for the installation and maintenance of offshore wind turbines. It also addresses the relevant regulations and standards governing offshore operations for floating wind turbines. Finally, this paper provides a forward-looking perspective on the installation and maintenance of floating wind turbines.